Pemanfaatan Media Sosial Instagram @brin_indonesia sebagai Media Komunikasi Publik di Badan Riset dan Inovasi Nasional (BRIN) - Rifana Dianti; Elpa Hermawan; Ondy Ondy (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine how the Instagram account @brin_indonesia is utilized as a medium for public communication by the National Research and Innovation Agency (BRIN). The background of this research is based on the high usage of social media in Indonesia, particularly Instagram, which offers significant opportunities for government institutions to establish more effective and efficient communication with the public. As a non-ministerial government agency, BRIN leverages Instagram as a strategic platform to disseminate information related to research, innovation, and science. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The data analysis refers to the theory of new media by Martin Lister et al., which includes six key characteristics: digital, interactive, hypertextual, virtual, networked, and simulation/convergence. The findings indicate that BRIN’s Instagram account functions not only as a one-way information channel but also as an interactive, educational, and representative digital space that supports institutional image and actively fosters public engagement in a structured manner.